The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s10904-023-02598-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Zeolite as a Carrier for Tumor Targeted and pH-responsive Drug Delivery

Abstract: In this work, for the first time, a material was prepared that releases the drug in a controlled manner under the influence of the pH of cancer environment. The material is zinc zeolite, which only releases the drug at an acidic pH. The release of the drug in an acidic environment indicates a very high potential of the synthesized material in the treatment of cancer. This material does not release the drug at pH 7.4 even for more than 100 h which proves that healthy organs will not be affected. The advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The dot plot confirmed that the zeolite-encapsulated Zn­(II) Salmphen shows higher selectivity toward the MCF7 cells than toward HaCaT and the images validate that the Zn­(II)­Salmphen complex resides majorly at the perinuclear region of the cells. The selective internalization of the zeolite-encapsulated Zn­(II)­Salmphen complex (Zn­(II)­Salmphen-Y) into MCF7 cells is probably because of the acidic microenvironment of cancer cells as one of the very recent studies reported that in comparison to a normal cellular environment, the release of drug molecules from the zeolite supercage was rapid and effective in a cancer environment …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dot plot confirmed that the zeolite-encapsulated Zn­(II) Salmphen shows higher selectivity toward the MCF7 cells than toward HaCaT and the images validate that the Zn­(II)­Salmphen complex resides majorly at the perinuclear region of the cells. The selective internalization of the zeolite-encapsulated Zn­(II)­Salmphen complex (Zn­(II)­Salmphen-Y) into MCF7 cells is probably because of the acidic microenvironment of cancer cells as one of the very recent studies reported that in comparison to a normal cellular environment, the release of drug molecules from the zeolite supercage was rapid and effective in a cancer environment …”
Section: Resultsmentioning
confidence: 99%
“…From the flow cytometric analysis, it is observed that internalization of Zn(II)Salmphen-Y was much better in cancer cells compared environment, the release of drug molecules from the zeolite supercage was rapid and effective in a cancer environment. 71 Evaluation of ROS Generation in Cancer and Noncancerous Cells. Overproduction of reactive oxygen species is considered a key factor in the death of cancer cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compared with the PLGA NPs, the PD-coated NPs had smoother release profiles. Notably, the NP release was greater under slightly acidic conditions, such as those typically found at tumor sites [4], suggesting a certain pH effect that would enable the NPs to better target the tumor site. PD NPs at pH 5.2 showed faster release at first.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…PD structures contain active double bonds that can chemically react with several groups, and a large number of sulfhydryl compounds can degrade the PD shell; thus, PD-encapsulated NPs can be degraded by glutathione when they enter the cells [48]. The PD coating's pH- Notably, the NP release was greater under slightly acidic conditions, such as those typically found at tumor sites [4], suggesting a certain pH effect that would enable the NPs to better target the tumor site. PD NPs at pH 5.2 showed faster release at first.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
See 1 more Smart Citation